hi i need to simplify this, but i don't know how to so can anyone help please?
Follow Math Help Forum on Facebook and Google+
Hello, $\displaystyle \left(\frac 23\right)^{-1}=\frac{2^{-1}}{3^{-1}}=\dfrac{\frac 12}{\frac 13}=\frac 12 \cdot \frac{1}{\frac 13}=\frac 12\cdot 3=\frac 32$ (to show as many steps as possible
Originally Posted by Moo Hello, $\displaystyle \left(\frac 23\right)^{-1}=\frac{2^{-1}}{3^{-1}}=\dfrac{\frac 12}{\frac 13}=\frac 12 \cdot \frac{1}{\frac 13}=\frac 12\cdot 3=\frac 32$ (to show as many steps as possible i know a bit of that but i don't understand how , please explain
Originally Posted by andyboy179 i know a bit of that but i don't understand how , please explain you should know $\displaystyle \frac{a}{b} / \frac{c}{d}$ $\displaystyle = \frac{a}{b} * \frac{d}{c}$ $\displaystyle \rightarrow$ $\displaystyle \frac{1}{2} / \frac{1}{3}$ $\displaystyle = \frac{1}{2} * \frac{3}{1}$
View Tag Cloud